Molecular Dynamic Simulation for Thermal Stability Properties of Endo Î²-Mannanase Enzyme - Yulandi, Adi; Hermosaningtyas, A A; Sutanto, Sheila; Suwanto, Antonius (UNEJ e-Proceeding, 2014)
Endo Î²-mannanase or mannanase hydrolyse the Î²-D-1,4 mannopyranoside linkages in Î²-mannan intomanno-oligosaccharides. Four mannanases, named MAN1, MAN2, MAN3 and MAN4, were isolated from palm kernel meal waste have potential as thermostable mannanases. Series of enzymatic assay to characterize enzyme properties may affect longer time and higher cost. Homology modeling and molecular dynamic simulation are reliable and faster alternative assay to determine enzyme properties by analyzing enzymesâ three-dimensional structure. The structureswere constructed using homology modeling approach using Modeller. Template 2QHA was chosen for having more than 98% sequence similarity with targets. The homology models and template were simulated using molecular dynamics software GROMACS 4.6 for 10 ns production time each at 300 K, 323 K and 353 K. Both targets share the same (Î²/Î±)8 TIM barrel folding type similar to template 2QHA The basic analysis of molecular dynamic simulation (root mean square deviation and root mean square fluctuation) showed that both enzymes were thermostable, albeit compared to template 2QHA amino acid residues substitution in samples contribute for different thermostable profile. However, MAN2 was appeared to be more stable at high temperature than other samples. Keywords: endo Î²-mananase, homology modeling, molecular dynamic simulation